Effect of Sustainable Fabric Sourcing on Fashion Brand Reputation in Sweden - Lindgren, Elsa (International Journal of Fashion and Design, 2024)
Purpose: The aim of the study was to analyze the effect of sustainable fabric sourcing on fashion brand reputation in Sweden Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Sustainable fabric sourcing has a positive impact on the reputation of fashion brands in Sweden. Brands that prioritize eco-friendly materials and ethical supply chains are increasingly seen as socially responsible, gaining consumer trust and loyalty. This shift reflects growing environmental awareness among Swedish consumers, who value transparency and sustainability in the fashion industry. As a result, brands that adopt sustainable practices often experience enhanced brand image, stronger customer relationships, and increased competitiveness in the market. However, the challenge lies in ensuring consistent implementation of these practices, as consumers are quick to criticize brands for "greenwashing" or failing to meet sustainability standards. Unique Contribution to Theory, Practice and Policy: Stakeholder theory, theory of planned behavior & resource-based view (RBV) may be used to anchor future studies on the effect of sustainable fabric sourcing on fashion brand reputation in Sweden. Brands should implement transparent communication strategies that detail their sustainable fabric sourcing practices. Policymakers should create supportive frameworks that incentivize sustainable sourcing practices in the fashion industry.